The Influence of Video Media on Improving Knowledge and Attitudes of Adolescent Girls Regarding Chronic Energy Deficiency - Sari, Riana Trinovita; Wulandari, Nadya; Siregar, Nursyahid; Amelia, Rizki; Supriatin, Supriatin (Yayasan Ahmad Mansyur Nasirah, 2025)
Adolescent girls are a vulnerable group to nutritional problems, particularly Chronic Energy Deficiency (CED), which can affect reproductive health and the quality of future generations. One of the main contributing factors to CED is the lack of knowledge and attitude toward nutrition. Video media is considered an effective educational tool as it combines engaging visual and audio elements. This study aimed to determine the effect of video media on improving the knowledge and attitudes of adolescent girls regarding CED at SMAN 4 Samarinda. The study employed a pre-experimental one-group pre-test post-test design with a sample of 39 eleventh-grade students selected through purposive sampling. The intervention consisted of a ±10-minute educational video on CED shown twice a week. Data were collected using questionnaires and analyzed using univariate and bivariate analysis with the Wilcoxon test. Results showed that most respondents were 16 years old (64.1%) and had a below-normal Body Mass Index (84.6%), indicating a risk of CED. The most common physical activity was participation in scouting (35.9%), followed by dance and volleyball. After the intervention, there was a significant increase in knowledge, from a median score of 10.00 to 13.00 (p = 0.002), and in attitude, from a median score of 31.00 to 33.00 (p = 0.001). These findings indicate that video media is effective in improving adolescents' understanding of CED. However, its effectiveness may also be influenced by age and prior access to information. Therefore, video media is highly recommended as a nutritional education tool in adolescent health programs.